Comparative evaluation of oral hygiene status by using oral hygiene index, simplified oral hygiene index, and modified oral hygiene index: Revalidation of modified oral hygiene index - Subhash Garg; Sumbul Nasir (Journal of Indian Society of Periodontology, 2024)
Background: Good oral hygiene is a critical component of overall oral health. Various methods have developed over time to assess oral hygiene status. In 1960, Greene and Vermillion introduced the Oral Hygiene Index (OHI), which assessed debris and calculus on 12 tooth surfaces. In 1964, they proposed a Simplified Oral Hygiene Index (OHI-S), which evaluated only 6 surfaces of six index teeth. The authors recommended the OHI-S due to its faster clinical assessments but concluded that it was less sensitive than the OHI despite both indices being sufficiently sensitive. In 1987, Garg S introduced the Modified Oral Hygiene Index (OHI-M), which provides a more comprehensive evaluation by assessing debris and calculus on the facial (buccal/labial), oral (palatal/lingual), and specifically occlusal surfaces of each fully erupted permanent tooth. The OHI-M is a reliable and sensitive method for accurately evaluating oral hygiene status. Aim: This study aims to comparatively evaluate oral hygiene status using OHI, OHI-S, and OHI-M and revalidate the OHI-M. Materials and Methods: 221 patients (119 males and 102 females) were randomly selected through simple random sampling. A single investigator performed the scoring. The sample size was determined based on a 95% confidence level. The collected data were analyzed using IBM SPSS Statistics, and Pearson’s correlation test was employed to assess the correlations. Results: The mean and standard deviation of the OHI-M were found to be the lowest (2.55 ± 0.82) compared to the OHI (7.13 ± 1.79) and OHI-S (3.23 ± 0.99). It indicates that the variation in OHI-M values is smaller than that in OHI and OHI-S. Positive correlations were observed among the three indices, with a statistically significant result (P < 0.001). Conclusion: The OHI-M is found to be the most sensitive scoring method for evaluating oral hygiene status compared to the OHI and OHI-S. These results further confirm the validity of OHI-M.